A High-Density Genetic Map and QTL Fine Mapping for Growth- and Sex-Related Traits in Red Swamp Crayfish (Procambarus clarkii) - Guo, Xin-Fen; Zhou, Yu-Lin; Liu, Min; Li, Zhi; Zhou, Li; Wang, Zhong-Wei; Gui, Jian-Fang (Frontiers in Genetics, 2022)
Red swamp crayfish (Procambarus clarkii) is a commercially important species in global aquaculture and most successfully invasive freshwater shrimp in China. In order to determine the genetic basis of growth and sex-related traits, a high-density genetic linkage map was constructed using 2b-RAD sequencing technology in a full-sib family. The consensus map contains 4,878 SNP markers assigned to 94 linkage groups (LGs) and spanned 6157.737 cM with an average marker interval of 1.26cM and the 96.93% genome coverage. The quantitative trait locus (QTL) mapping for growth and sex traits was performed for the first time. QTL mapping uncovers 28 QTLs for growth-related traits in 9 LGs, explaining 7.9%-14.4% of the phenotypic variation, and identifies some potential candidate growth-related genes such as mih, lamr, golgb1, nurf301 and tbcd1 within the QTL intervals. A single major locus for sex determination was revealed in LG20 that explains 59.3-63.7% of the phenotypic variations. Some candidate sex-related genes, such as vps4bl, ssrf and acot1, were identified in the QTL intervals and found to be differential expressed in the muscle tissues between the females and the males. What’s more, the identified SNPs were revealed to be female heterozygotes, suggesting that red swamp crayfish might have the female heterogametic ZZ/ZW sex determination system. The present study provides a valuable resource for marker-assisted selection and genetic improvement, and for further genetic and genomic researches in red swamp crayfish.